Genetically confirmed clinical Huntington's disease with no observable cell loss. Issue 7 (1st July 2003) - Caramins, M; Halliday, G; McCusker, E; Trent, R J
Abstract : Huntington's disease (HD) results from neurodegeneration of the neostriatum. The mutation on chromosome 4 is an expansion in a triplet repeat (CAG)n located within the IT15 gene. Only six patients have been reported with clinical features of HD in association with limited neuropathology. Of these, only one has had the diagnosis confirmed by genetic (DNA) testing. We describe a patient with the clinical phenotype and genetically confirmed HD but unexpected limited neuropathology. The patient was seen because of aggressive behaviour and memory problems of two years duration. The differential diagnosis included HD although there was no family history. DNA testing was positive for the HD mutation. Clinical follow up three months later confirmed classic features of HD. Progression of the disease was rapid with death three years later. Neuropathology revealed a largely intact neostriatum with bilateral ischaemic damage and cell loss in the external globus pallidus. Such pathology alone could explain the clinical features of HD. This is only the second report of genetically confirmed clinically manifest HD with little evidence of HD neuropathology. There are several unusual features which could not have been predicted by the clinical picture, in particular the progressive course of bilateral ischaemic changes restricted to the external globus pallidus. The potential to miss other HD cases at post-mortem examination, and the implications of this for family members, are discussed.